COMING BACK TO MOCKINGBIRD AFTER FIVE DECADES (International journal of artificial intelligence, 2025)
The current article explores the return of “To Kill a Mockingbird” (1960) by American novelist Harper Lee, in “Jasper Jones” by Australian writer Craig Silvey (2009). The two novels are analyzed by contextual connection. Both novels employ the coming-of-age genre, sharing ample similarities. However, there are noticeable differences between the two. The current article deals with relationships between the two novels by analyzing the recurrence of the symbol of “Mockingbird”. It first deals with protagonists’ Losing Innocence, then extends to Social Racism towards the Vulnerable Heroes in both novels, and finalizes with varieties at the end of the day.